ANALYZING OF SYSTEM USABILITY SCALE IN USER EXPERIENCE EVALUATION OF DANA APPLICATIONS - Fuaida, Famrotul; Prasojo, Bayu Hari; Racmadany , Andry; Almanfaluti , Istian Kriya (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The rapid development of financial technology (FinTech) has transformed how individuals conduct financial transactions, particularly through e-wallets. Dana, one of the leading e-wallet applications in Indonesia, has garnered significant attention due to its widespread usage and user feedback. Method: This study evaluates the user experience (UX) of the Dana application using the System Usability Scale (SUS) that provides a quick and quantitative measure of usability, Data were collected from 153 respondents through a questionnaire. Results: The SUS analysis yielded an average score of 65. According to SUS interpretation scales, this score categorizes Dana as "Marginal" in Acceptability Ranges, "C" on Grade Scale, and "OK" on Adjective Rating, with users classified as "Passive" based on Net Promoter Score (NPS). Novelty: This study emphasizes the importance of systematic UX evaluation in identifying user needs and evaluation for the app, providing actionable recommendations to improve the Dana application. These recommendations aim to enhance usability, user satisfaction, and competitiveness in the FinTech sector.